The development and test retest reliability of Malaysia Smell Test (MAST)/ Ainaa Syahidah Zulkefli and Akehsan Dahlan - Zulkefli, Ainaa Syahidah; Dahlan, Akehsan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Background: Olfaction has an essential role in daily life. A decline in the olfactory function could possibly be an early signal of neurodegenerative disorders such as Alzheimer’s disease. Currently, there are few smell test that have been developed but not all test are appropriate in different regions due to the cultural differences. Objective: To develop and validate the Malaysia Smell Test (MAST) for elderly population in Malaysia. Study design: Cross sectional study. Method: A market survey on healthy elderly people (n = 125) was performed to identify familiar odours remembered among elderly people in Malaysia. Ten odours were selected and the MAST kit was developed using raw material. MAST was tested on 38 subjects and repeated after two weeks. All data was analysed using SPSS version 21. Result: There was a statistically significant differences in MAST score from test and retest (p=0.003). Test-retest study revealed that MAST is a reliable test (Spearman’s rank correlation coefficient between test-retest identification scores: r=0.93), ICC value of 0.92 and Kappa value of 0.31. Conclusion: Although MAST has significant differences between test and retest, the time stability appears to be consistent and reliable over time. There was no changes in odour identification during time interval.